All Days 2011
DOI: 10.2118/142700-ms
|View full text |Cite
|
Sign up to set email alerts
|

Inflow Control Devices Minimize Annular Velocity in Gas Wells with Stand-Alone Screen Completions

Abstract: Many gas wells in unconsolidated sandstone reservoirs have been completed with stand-alone screens (SAS) that use either wire-wrapped screens (WWS) or mesh screens. This method is a cost-effective sand-control method for completions, especially in horizontal (Hz) wells where gravel packing (GP) may not be attractive for economic, operational, or logistical reasons. Because there are annular-flow failure concerns with this type of completion, a simple well-modeling study was conducted to look at the potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moreover, they stated that, 'sand screen erosion is a process where a huge number of discrete particles erode a screen at multi-angle in the turbulent regime'. Other studies such as those conducted by Greene and Moen (2012) and Regulacion and Shahreyar (2011) found that annular flow plays an essential role in the erosion and failure of sand screens in horizontal gas wells. However, Gillespie et al (2009) attributed early life failures of the screen to severe plugging with solids in a drilling fluid, which could have occurred during installation.…”
Section: Mechanism Of Screen Erosionmentioning
confidence: 91%
“…Moreover, they stated that, 'sand screen erosion is a process where a huge number of discrete particles erode a screen at multi-angle in the turbulent regime'. Other studies such as those conducted by Greene and Moen (2012) and Regulacion and Shahreyar (2011) found that annular flow plays an essential role in the erosion and failure of sand screens in horizontal gas wells. However, Gillespie et al (2009) attributed early life failures of the screen to severe plugging with solids in a drilling fluid, which could have occurred during installation.…”
Section: Mechanism Of Screen Erosionmentioning
confidence: 91%
“…They stated that ‘the sand screen erosion is a process of a huge number of discrete particles eroding screen at multi-angle in the turbulent regime’. Greene and Moen [ 79 ] and Regulacion & Shahreyar [ 80 ] have noted that in horizontal gas wells, annular flow is a critical factor contributing to the erosion and failure of sand screens. Similarly, Gjedrem [ 70 ] found that high annular velocity tends to cause of extreme screen erosion.…”
Section: Sand Screen Integrity and Failurementioning
confidence: 99%